2013
DOI: 10.1590/s1414-81452013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Alta hospitalar e o cuidado do recém-nascido prematuro no domicílio: vivência materna

Abstract: Objetivou-se conhecer a percepção da mãe sobre a alta hospitalar e o cuidado do recém-nascido prematuro no domicílio após a primeira semana de alta. Pesquisa descritiva, de abordagem qualitativa, com uso da entrevista semiestruturada para coleta de dados, desenvolvida no ambulatório de seguimento do prematuro (follow-up) do Hospital da Rede Pública Estadual de Fortaleza, em outubro e novembro de 2011. As participantes foram nove mães de recém-nascido prematuro após primeira semana de alta. Aplicou-se análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 12 publications
1
23
0
30
Order By: Relevance
“…The results of the clinical application of Preterm Parenting & Self-Efficacy Checklist -Version 3 identified that perceiving the ability to change a diaper of a premature infant; perceiving the importance of understanding the infant signs; dealing with restlessness and crying; and feel successful in the task of giving a bath were statistically significant related with the maternal figure. Such aspects about the development of parenting in the neonatal unit were evidenced in other investigations (25)(26) , reinforcing that mothers who are prepared for hospital discharge show reduced anxiety and increased self-confidence in providing care to premature infants at home.…”
Section: Discussionmentioning
confidence: 54%
“…The results of the clinical application of Preterm Parenting & Self-Efficacy Checklist -Version 3 identified that perceiving the ability to change a diaper of a premature infant; perceiving the importance of understanding the infant signs; dealing with restlessness and crying; and feel successful in the task of giving a bath were statistically significant related with the maternal figure. Such aspects about the development of parenting in the neonatal unit were evidenced in other investigations (25)(26) , reinforcing that mothers who are prepared for hospital discharge show reduced anxiety and increased self-confidence in providing care to premature infants at home.…”
Section: Discussionmentioning
confidence: 54%
“…This empowerment is largely due to qualified nursing care in health education and promotes health in childhood, preventing injuries and contributing to the reduction of neonatal mortality, which accounts for 40% of infant mortality and is still a major challenge in the health area. (22,23) It is essential to discuss accessible education strategies and technologies that involve the community and grant it an active and essential role in knowledge construction, valuing background knowledge and questions. (4,5,8) As a limitation of this study, we point out the sample size and suggest that future studies verify learning retention or, if possible, observe its application in the families' daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…(7) In this context, the planned discharge along with family and home visits of nurses helped reduce anxiety and fear. (16) Home care is based on interaction among health professionals, patients and their relatives, and it seeks to improve the autonomy and highlight skills of individuals by using educational actions, demonstration and/or execution of procedures in the families environment -their homes. (17,18) In patients' home, the professionals can understand the reality of the supported individuals, recognize their problems and needs (17) and, in this way, adapt the knowledge and technical procedures to home care.…”
Section: Discussionmentioning
confidence: 99%